Physics at the Munich Tandem Accelerator Laboratory. (2nd January 2018) - Dollinger, Günther; Faestermann, Thomas
Abstract : The Tandem accelerator situated in Garching, just 20 km north of Munich, is of the "Emperor" (MP) series manufactured by High Voltage Engineering Corporation (HVEC). It delivered the first beams for experiments in 1970 and came close to its design voltage of 10 MV. In 1991 the tubes were exchanged to the extended version of HVEC. Routine operation at a terminal voltage of 14 MV was then possible.